2020
DOI: 10.1093/jac/dkaa176
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose pharmacokinetics of temocillin in plasma and soft tissues of healthy volunteers after intravenous and subcutaneous administration: a randomized crossover microdialysis trial

Abstract: Background The antibiotic temocillin has recently been rediscovered as a promising therapeutic option against MDR Gram-negative bacteria. However, some aspects of the pharmacokinetic (PK) profile of the drug are still to be elucidated: subcutaneous administration of temocillin might be of interest as an alternative to the intravenous route in selected patients. Similarly, information on the penetration of temocillin into human soft tissues is lacking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The plasma unbound concentration of temocillin was best described by a two-compartment model, as previously published [ 32 ], and an additional compartment was added to describe unbound concentration in ascitic fluid (-2LL = 1497, AIC = 1514). Ascitic fluid was eliminated via a drain, thus, non-renal elimination from this additional compartment (CL30) was associated with a significant reduction of -2LL and AIC (Δ-2LL = 10, AIC = 1506).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma unbound concentration of temocillin was best described by a two-compartment model, as previously published [ 32 ], and an additional compartment was added to describe unbound concentration in ascitic fluid (-2LL = 1497, AIC = 1514). Ascitic fluid was eliminated via a drain, thus, non-renal elimination from this additional compartment (CL30) was associated with a significant reduction of -2LL and AIC (Δ-2LL = 10, AIC = 1506).…”
Section: Resultsmentioning
confidence: 99%
“…For highly protein-bound drugs, including antibiotics, it is commonly admitted that the unbound drug is responsible for the activity [ 27 , 28 , 29 ]. In this context, it is important to note that temocillin shows a saturable and highly variable [ 30 , 31 ] plasma protein binding, ranging from around 85% in adult healthy volunteers [ 15 , 32 ] to a mean value of 59% (range: 19 to 85%) in critically-ill patients [ 33 ]. A previous PK study in critically-ill patients showed that a daily dose of 6 g given as continuous infusion allows to sustainably maintain unbound serum concentrations above 16 mg/L in the vast majority of the patients [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a PK/PD perspective, SC administration is especially interesting for the administration of beta-lactam drugs, as it results in time above the MIC similar if not greater than IV administration of the same dose (3)(4)(5)8). This suggests that SC administration of beta-lactams should be as efficient as IV administration, although there is a dearth of high-level clinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Spacing drug administration is desirable in this setting, but it should respect the PK/PD requirements of each drug to ensure treatment efficacy. It has been shown that the subcutaneous (SC) route may facilitate drug administration in patients compared with IV route, while preserving the PK/PD objectives of beta-lactams (3)(4)(5)(6)(7)(8). Combining infrequent administration and SC route could be a way to facilitate prolonged suppressive outpatient therapy with beta-lactams, but there is limited information on this practice.…”
Section: Introductionmentioning
confidence: 99%
“…SC administration of ampicillin, cefepime, and temocillin present a similar PK profile to that of the other studied antibiotics, characterized by a delayed T max but similar AUCs. 45,49,65 However, these studies were performed in healthy volunteers and with single-dose PK analysis.…”
Section: Other Antibioticsmentioning
confidence: 99%